When Did God Create Hell? - Amukowa, Wycliffe (MCSER-CEMAS-Sapienza University of Rome, 2013)
The concept of hell as a place for eternal punishment is a central theme in both Christianity and Islam. The followers of these religions believe that after the last judgment all wrongdoers (sinners) will be consigned to hell to suffer everlasting punishment, while non-sinners will go to heaven to enjoy a life of everlasting happiness (Mbugua 2011). This paper attempts a dismissal of the existence of Hell.
Keywords: Heaven; God; Sin; Hell; Punishment; Eternal